2020
DOI: 10.4236/oalib.1106043
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Male Involvement in Family Planning Services: A Case Study in the Tema Metropolis, Ghana

Abstract: Background: Usage of family planning services in developing countries has been found to avert unintended pregnancies, and drastically reduce maternal and child mortality. Men as the main decision-makers in most of African families have an important role to play towards acceptance of family planning methods; however, its usage still remains low. The primary objective of this study was to investigate the factors that influence male involvement in family planning. Method: This was a descriptive cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
4
3
0
Order By: Relevance
“…According to this review, the national pooled prevalence of male involvement in FP was 39.7%. This finding was consistent with a study conducted in Turkey, 33 Ghana (34.4%), and (38.9%), 34,35 and Uganda (40%). 36 However, the level of male involvement in FP was lower than a study conducted in Bangladesh (63.2%), 37 Vietnam (63.7%), 38 Kenya (52%), 39 Nigeria (89%), 40 and India (71.2%).…”
Section: Discussionsupporting
confidence: 93%
“…According to this review, the national pooled prevalence of male involvement in FP was 39.7%. This finding was consistent with a study conducted in Turkey, 33 Ghana (34.4%), and (38.9%), 34,35 and Uganda (40%). 36 However, the level of male involvement in FP was lower than a study conducted in Bangladesh (63.2%), 37 Vietnam (63.7%), 38 Kenya (52%), 39 Nigeria (89%), 40 and India (71.2%).…”
Section: Discussionsupporting
confidence: 93%
“…Knowledge about FP will influence acceptance and therefore impact involvement of men in its utilization. Similar studies by [ 26 , 27 ] have found FP knowledge to be positively linked with its utilization. Our study additionally revealed that men who had greater than two living children were more likely to be involved in FP service utilization.…”
Section: Discussionsupporting
confidence: 85%
“…Male spouses currently employed in the same vein are assumed to have a social life outside the home, which might have limited their sentiment on non-FP use. Studies conducted in Ghana [19] and Angola [11] also corroborate the study's result.…”
Section: Discussionsupporting
confidence: 82%